2012
DOI: 10.1021/pr300454f
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Investigation of the Anti-Platelet Aggregation Activity of Ginsenoside Rk1 Reveals Attenuated 12-HETE Production

Abstract: Comprehensive metabolomics analysis is an effective method of measuring metabolite levels in the body following administration of a pharmaceutical compound and can allow for monitoring of the effects of the compound or assessment of appropriate treatment options for individual patients. In the present metabolomics study, samples pretreated with antiplatelet compounds were extracted and subjected to ultraperformance liquid chromatography/quadrupole time-of-flight mass spectrometry. The acquired data were proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 36 publications
0
48
0
Order By: Relevance
“…Significant differences were found in IL-1β, IL-2, IL-4, TNF-α, and histamine via the treatment of glycoproteins. In the Morris water maze test, the glycopeptides effectively alleviated the memory impairment symptoms of rats induced by Aβ [25][26][27][28][29][30][31][32][33][34][35] , and they showed significant protective activity against the apoptosis of SH-SY5Y neuronal cells induced by Aβ [25][26][27][28][29][30][31][32][33][34][35] [35].…”
Section: Ginsenosides In Anti-inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant differences were found in IL-1β, IL-2, IL-4, TNF-α, and histamine via the treatment of glycoproteins. In the Morris water maze test, the glycopeptides effectively alleviated the memory impairment symptoms of rats induced by Aβ [25][26][27][28][29][30][31][32][33][34][35] , and they showed significant protective activity against the apoptosis of SH-SY5Y neuronal cells induced by Aβ [25][26][27][28][29][30][31][32][33][34][35] [35].…”
Section: Ginsenosides In Anti-inflammationmentioning
confidence: 99%
“…Ginsenoside Rk1 was also found to exhibit a strong inhibitory effect on arachidonic acid-induced platelet aggregation [29]. Decreased productions of thromboxane B 2 , a key element in platelet aggregation, and 12-hydroxy-5,8,10,14-eicosatetraenoic acid (12-HETE), an arachidonic acid metabolite, were observed in the ginsenoside Rk1-treated platelets via inhibition of COX activity and 12-lipoxygenase translocation resulting from decreased Ca 2+ levels [29].…”
Section: Ginsenosides In Anti-inflammationmentioning
confidence: 99%
“…These reports also suggest that the inhibitory action of ginseng saponins on platelet activation might be caused by increased cyclic AMP levels. Recently, it has been reported that newly isolated ginseng saponins and metabolites (Rk1, Rk3, Rg5, Rg6, Rh4, Rs3, Rs4, Rs5, and F4) exert antiplatelet activities [21][22][23], but the mechanism is still unclear. Therefore, it will be investigated whether the new ginseng compounds on cyclic AMP level in human platelets.…”
Section: Discussionmentioning
confidence: 99%
“…Out of the 21 studies included, 16 studies were related to the effectiveness of G-Rk1 only and five studies were reported on the combined effects of G-Rk1 and G-Rg5. The most common study design was in vitro study with 16 studies (Kim et al 2008;Ko et al 2009;Lee et al 2010;Park et al 2002;Lim et al 2009;Jing et al 2006;Kim et al 2012;Bao et al 2005;Ju et al 2012;Liu et al 2007;Park et al 2015;Kim et al 2010;Kang et al 2006;Siddiqi et al 2014;Kang et al 2007), while in vivo study was less common with only two studies (Toh et al 2011;Erb et al 2005). The remaining three articles were both in vitro and in vivo study (Lee.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…We used the GRADE method (Guyatt et al 2011) to assess the quality of the included studies. Ten studies (Bao et al 2005;Jing et al 2006;Ju et al 2012;Kang et al 2007;Kim et al 2012;Kim et al 2010;Lee et al 2010;Park et al 2015;Siddiqi et al 2014) were categorized as moderate quality. Five of them (Bao et al 2005;Jing et al 2006;Park et al 2015;Siddiqi et al 2014) were focusing on the effectiveness of combined (G-Rk1, G-Rg5), thus, they were downgraded in indirectness item of GRADE factors.…”
Section: Risk Of Bias Across Studiesmentioning
confidence: 99%